Effect of Self-Efficacy and Peer Social Support on Students’ Career Maturity - Putri Sundari Hanifa; Dwi Yuwono Puji Sugiharto; Mulawarman (Study Program of Guidance and Counselling, Post Graduate Program, Universitas Negeri Semarang, 2024)
The part of the phenomena of vocational high school students' (SMK) perplexity about their future profession options are attributed to their immaturity and lack of preparedness for the workforce. With an ex post facto study using a sample of 280 students from SMKN 6 Kota Semarang, the purpose of this research is to investigate the impact of peer social support and self-efficacy on their career maturity. Multiple linear regression analysis was used to test the research findings, and the results show that career maturity is highly affected by self-efficacy. In a similar vein, career maturity is greatly affected by peer social support. Thus, career maturity is affected by both peer social support and self-efficacy combined. These results help to clarify the requirements and difficulties faced by students when selecting their future careers, allowing for more targeted and efficient counseling.